P520 Gastrointestinal ultrasonography in pregnant patients with IBD is useful in the identification of active intestinal inflammation. (16th January 2018) - Flanagan, E; Wright, E; Begun, J; Bryant, R; Sathananthan, D; Bell, S
Abstract: Background: Many patients with inflammatory bowel disease (IBD) are in their child-bearing years. Active IBD can lead to adverse pregnancy outcomes. It is therefore imperative to monitor patients with IBD accurately and safely during pregnancy. Gastrointestinal ultrasonography (GIUS) can accurately identify disease activity and extent in patients with IBD. As a radiation free and non-invasive imaging modality, GIUS is the safest imaging technique for use in pregnancy. However, the feasibility and accuracy of GIUS throughout pregnancy has not been evaluated. Accordingly, we aimed to determine the feasibility and accuracy of GIUS in the assessment of IBD in pregnancy. Methods: A multicentre observational study across three Australian GIUS centres evaluated the efficacy of GIUS for monitoring IBD in pregnancy. Clinical information including disease phenotype and inflammatory biomarkers (CRP and faecal calprotectin) were recorded. GIUS findings were recorded including bowel wall thickness (BWT) and colour Doppler blood flow, from which the Limberg score was calculated. BWT > 3 mm with or without increased colour Doppler blood flow was defined as active disease. Clinicians made an assessment of bowel views (adequate/inadequate) for each colonic segment (sigmoid, descending, transverse, ascending) and the terminal ileum (TI). Results: Thirty-three pregnant patients were included. Median patient age was 31 years (IQR 25–33). Median gestation at GIUS was 18 weeks (4–30). 64% (21 of 33) of patients had Crohn's disease (CD); the most common disease location was ileal CD in 43%. 36% (12 of 33) had ulcerative colitis (UC) (58% with left sided and 42% with pan-UC). With respect to feasibility, in the first trimester of pregnancy (<12 weeks), adequate views were obtained in all bowel segments in all examinations (11 scans). Fifteen scans were performed at 12–24 weeks with adequate views obtained in all segments except in 2 of these scans (at 18 and 22 weeks) where TI views were inadequate. In examinations performed at 25–30 weeks (7 scans), TI views were inadequate but left colon views were adequate. Active IBD was detected using GIUS in 6 patients (Median BWT 5.1mm, Limberg score 1–3). These findings accurately correlated with inflammatory biomarkers. Conclusions: GIUS is a feasible and accurate modality for monitoring IBD in pregnancy. During the first trimester complete views of the colon and TI were universally obtained. Complete assessment was obtained in the majority of patients up to 24 weeks. Beyond 24 weeks GIUS provides good views of the left colon but the remainder of the colon and TI are difficult to assess with confidence. Active IBD is accurately identified by GIUS in pregnancy. We advocate for increased uptake of GIUS in pregnancy to monitor disease activity in IBD.